Competency Analysis of Technological Pedagogical and Content Knowledge (TPACK) Biology Teachers - Nuruzzakiah Nuruzzakiah; Hasanuddin Hasanuddin; Wiwit Artika; Supriatno Supriatno; Hafnati Rahmatan (Postgraduate, University of Mataram, 2022)
TPACK competence of teachers can improve the quality of learning in accordance with the demands and changes. Information on TPACK competencies is needed regarding the ability of teachers to know the professional development of teachers. This study aims to determine the competence criteria of biology teachers in Aceh Province in the components of CK, TK, PK, PCK, TCK, TPK, and TPACK, to find out the significant differences in TPACK competence of biology teachers based on teacher certification and teaching experience. This type of research is descriptive with a quantitative approach. The population in this study were all Biology teachers at state high schools in Aceh Province, namely civil servants, and non-civil servants, totaling 692 teachers. Sampling using a simple random sampling technique, obtained 232 respondents which is a total of 33.53% of the number of teachers in each district. The research instrument in the form of a questionnaire was adapted from Schmidt which consists of 38 items and has gone through face validity. Data analysis for the TPACK component is described according to the predicate criteria. The TPACK competence of biology teachers based on certification was analyzed by independent sample t-test, while the TPACK competencies of biology teachers based on teaching experience were analyzed using ANOVA. The results showed that the highest competency criteria for the TPACK component were PK with a score of 83.35% (very good), while the lowest was TK with a score of 76.84% (good). The results also showed that there was no significant difference (p> 0.05) in the TPACK competence of biology teachers based on certification and teaching experience